2022
DOI: 10.1088/1755-1315/950/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

Climate Suitability for Paddy in Sukabumi Regency by 2032 Using RCP 4.5 Scenario

Abstract: Climate is the crucial determining component in defining the land suitability class for paddy. The paddy suitability class is expected to decrease as a result of global climate change. This study analyzed land suitability for paddy based on the Representative Concentration Pathways (RCP) 4.5 climate projection scenario of Sukabumi Regency in 2020 and 2032 using the Model for Interdisciplinary Research on Climate (MIROC) 5. The parameters analyzed were precipitation (pr), and near-surface air temperature (tas).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…The selection of RCP scenarios depends on the interests and considerations of each published report. The RCP4.5 scenario is predicted to occur, as stated by W Siska et al [28] in the usage of the RCP4.5 scenario. RCP4.5 assumes that all nations participate in GHG reduction initiatives concurrently and successfully [32].…”
Section: Scenariomentioning
confidence: 87%
See 2 more Smart Citations
“…The selection of RCP scenarios depends on the interests and considerations of each published report. The RCP4.5 scenario is predicted to occur, as stated by W Siska et al [28] in the usage of the RCP4.5 scenario. RCP4.5 assumes that all nations participate in GHG reduction initiatives concurrently and successfully [32].…”
Section: Scenariomentioning
confidence: 87%
“…all [25] evaluated the projections of rice productivity in mainland Java with two other studies were conducted in the Keduang Subwatershed, Central Java [26] and West Nusa Tenggara [27]. By 2022, at the time of this review is authored, the only research on land suitability analysis for rice farming that uses RCP4.5 scenario is conducted in Sukabumi District to assess the effect of climate changes projected between 2020 [28]. In conducting this research, regional climate model (RCM) and processing of the model data are used to produce a projection of future climate change on a regional scale.…”
Section: Climate Change Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Climate in this case precipitation and temperature are important determinants in determining land suitability classes [6]. There are four criteria for the suitability of…”
Section: Temperaturementioning
confidence: 99%
“…Climate change can also affect crops, livestock, land and water resources, rural communities, and agricultural workers [10]. A study conducted to determine the suitability of the climate for rice cultivation in Sukabumi Regency in 2032 found that there will be no change in the suitability class of iklim for rice cultivation [11]. Another study simulated adaptation strategies to offset the potential impacts of climate variability and change on outcomes in Embu District, Kenya [12].…”
Section: Introductionmentioning
confidence: 99%